Comparação dos efeitos do treinamento físico com supervisão, sem supervisão e por meio da telerreabilitação na função cardiovascular, capacidade funcional e qualidade de vida de pacientes com insuficiência cardíaca - Silva, Esther Munerato Figueira da (Universidade Federal de São Carlos, 2023)
Heart failure (HF) is a state in which the heart is no longer able to meet the circulatory needs of the body, being the consequence of most diseases of the cardiovascular system and one of the main reasons for mortality, hospitalizations and impaired quality of life. There are several therapeutic strategies through the use of drugs or medical devices that aim to reduce mortality caused by cardiovascular diseases (CVDs). However, the magnitude of the benefits of physical training programs carried out in different scenarios is not yet well elucidated in the literature, including training based on the presence of a physical education professional within heart failure clinics, performing non-prescription exercise supervised compared to a supervised face-to-face training program or telerehabilitation. Furthermore, it is known that impairment of cardiac function assessed by echocardiography can adversely impact the exercise tolerance of patients with HF, making it important to detect echocardiographic variables capable of detecting low functional capacity in these patients. The work was divided into two studies with the objective of detecting echocardiographic variables with good accuracy for low exercise tolerance in patients with heart failure with reduced ejection fraction (HFrEF) and comparing the effects of physical training with supervision, without supervision and telerehabilitation with supervision on function cardiovascular disease, functional capacity and quality of life (QoL). Study 1 was a prospective cross-sectional study involving 50 patients, mean age 62 ± 11 years, 65% men. There was an association between diastolic function variables E’ Mitral Septal (R = 0.55 and P < 0.001) and E/E’ Mitral (R = 0.30 P = 0.031) with shorter distance in the 6MWT and impaired QoL. E’ Mitral Septal, adjusted for a model of age and ejection fraction, was an independent marker of poor exercise tolerance (R=0.57; p<0.001). The ROC curve showed the cutoff E’ Mitral Septal < 5.8 cm/s with A/C of 0.74 [CI: 0.60-0.88; p=0.01], sensitivity of 68% and specificity of 79% for the shortest distance covered in the 6MWT. Thus, E’ Mitral Septal, in the considered sample, has good accuracy for detecting low exercise tolerance in patients with HfrEF. Study 2 was a longitudinal clinical trial with a sample of 18 patients divided into 3 groups. There was no difference between groups in relation to pre-intervention characteristics, with the final sample comprising 55% males, with a mean age of 62 ± 12 years. There was an improvement in left ventricular ejection fraction (LVEF) (P=0.002), in the distance covered in the 6MWT (P<0.001) and in QoL (P<0.001) considering the effect of time. There was interaction between time and group in skinfold values for muscle groups: biceps (P=0.04), triceps (P=0.01), chest (P=0.05) and thigh (P=0.01; P=0.03). There was a significant association between improvement in the distance covered in the 6MWT and in QoL (R=0.53; P<0.001). A favorable impact of physical training on cardiac function, exercise tolerance and QoL was observed in patients with HFREF. Regarding the comparison between the groups, although the sample is limited, no significant difference was observed between them.
Comparison of the effects of physical training with supervision, without supervision and through telerehabilitation on the cardiovascular function of patients with heart failure
Keywords: Teste de caminhada de 6 minutos; Exercício físico; Disfunção sistólica; Qualidade de vida; Pressão de enchimento do ventrículo esquerdo; 6-minute walk test; Physical exercise; Systolic dysfunction; Quality of life; LV filling pressure; CIENCIAS DA SAUDE::EDUCACAO FISICA